Digital Bodleian - Bodleian Library (2015)
[Dt.:] Digital.Bodleian ermöglicht den Zugriff auf die verschiedenen Sammlungen der Boleian Library. - [Engl.:] Digital.Bodleian is bringing together the discrete collections of the Bodleian Library under a single user interface which supports fast user-friendly viewing of high resolution images. There is a standard metadata set for each collection to facilitate faceted browsing and searching across collections. The database provides an OAI-PMH target and the ability to machine-read and harvest these collections. Ans it allows users to tag and annotate images and group together content into their own virtual collections which can be shared with other users. As user, you can export metadata and images.